2010
DOI: 10.1016/j.jfms.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction survey of feline haemoplasma infections in Greece

Abstract: The aim of this study was to use real-time polymerase chain reaction assays to determine the prevalence of three haemoplasma species in cats from Greece and to evaluate possible associations between haemoplasma infection and age, gender, feline immunodeficiency virus/feline leukaemia virus (FIV/FeLV) status and packed cell volume (PCV). Ninety-seven cats (24 ill anaemic, 55 ill non-anaemic, 18 healthy non-anaemic) were included in the study. Twenty cats (20.6%) were haemoplasma positive; seven cats were infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
27
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 31 publications
18
27
3
Order By: Relevance
“…This supports the previous reports that retroviral infections, especially FIV, are risk factors for haemoplasma infection [43, 46]. Consistent with previous studies [40, 4547], our study also identified additional risk factors including age (OR = 1.1, 95% CI: 1.1–1.2, P  = 0.017) and being a shelter-feral cat (OR = 2.8, 95% CI: 1.1–7.4, P  = 0.043) for CMhm infection, and access to outdoors (OR = 8.7, 95% CI: 1.9–39.1, P =0.005) for infection with any haemoplasma species. Interestingly, this is the first time L. infantum infection in cats (OR = 7.3, 95% CI: 1.4–37.5, P  = 0.018) has been associated with CMt infection, with Leishmania infected cats being seven times more likely to be CMt-positive.…”
Section: Discussionsupporting
confidence: 93%
“…This supports the previous reports that retroviral infections, especially FIV, are risk factors for haemoplasma infection [43, 46]. Consistent with previous studies [40, 4547], our study also identified additional risk factors including age (OR = 1.1, 95% CI: 1.1–1.2, P  = 0.017) and being a shelter-feral cat (OR = 2.8, 95% CI: 1.1–7.4, P  = 0.043) for CMhm infection, and access to outdoors (OR = 8.7, 95% CI: 1.9–39.1, P =0.005) for infection with any haemoplasma species. Interestingly, this is the first time L. infantum infection in cats (OR = 7.3, 95% CI: 1.4–37.5, P  = 0.018) has been associated with CMt infection, with Leishmania infected cats being seven times more likely to be CMt-positive.…”
Section: Discussionsupporting
confidence: 93%
“…The highest overall prevalence of haemotropic mycoplasmas in Europe (43.4%) was found in a recently reported study from Portugal, where all four feline haemotropic mycoplasmas were identified, with all four mycoplasmas co-infecting one cat [76]. In line with some other studies, male sex [69,71,72] and older age [16,71,77,78] were found significantly associated with the detection of haemotropic mycoplasma DNA in the cats from Tirana. Contradictory to Gentilini et al (2009), who suggested an association of summer season and higher prevalence of feline haemotropic mycoplasma infection because of a higher ectoparasite load which facilitates vectorial transmission of infections, own data and results of studies from Germany and Portugal [72,76,79] do not indicate a positive correlation of the presence of blood-feeding arthropods and feline haemoplasmosis.…”
Section: Discussionsupporting
confidence: 72%
“…Feline haemotropic mycoplasma infections are believed to have a worldwide distribution with variable prevalence in the different populations of cats [69,70]. For Albania, this is the first study to document the occurrence and prevalence of three haemotropic mycoplasmas in cats, and it is the only other study on feline haemotropic mycoplasma infection from the Balkans beside one report from Greece [71]. The overall proportion of haemotropic mycoplasma infection of almost 31% as well as the prevalence of the individual mycoplasmas, including the percentage of co-infections, were within the range of results obtained in other studies in Europe [71-75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of feline hemoplasma species found was similar to that found in client-owned cats, blood donor cats and unhealthy non-anemic cats (GENTILINI et al, 2009;MAHER et al, 2010;SANTOS et al, 2014;DUARTE et al, 2015). However, higher or lower rates of hemoplasma infection have been reported, depending on the diagnostic technique, geographical location and population studied.…”
Section: Discussionsupporting
confidence: 71%